Some studies into the effects of metaldehyde on cultured cells - Salmijah Surif,; Anita Mohd. Zubir,; Maimon Abdullah, (Universiti Kebangsaan Malaysia, 1997)
Metaldehyde is used widely in Malaysia for the control of molluscs. This communication reports the cytotoxic effects of this chemical on cultured cells as assessed by cell morphology and the DNA synthesing capability as well as its transport into cells. After 15 days of exposure with 20.0 ppm of the compound, the DNA synthesising capability was shown to be unaffected. The IC50 for Vero cells was 276.0 ppm. Transport of thymidine across cells was found to be not significantly affected even at high metaldehyde concentrations (up to 320.0 ppm) suggesting integrity of cells were not significantly affected. The present cellular studies have therefore shown that the cytotoxic effects of this chemical is rather low.